PENGEMBANGAN MODUL FISIKA GELOMBANG BUNYI BERBASIS REACT UNTUK KELAS XI IPA - Syindi Isna Maulida; Trapsilo Prihandono; Maryani Maryani (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract The objectives of this study are: 1) developing sound wave physics module based on REACT for class XI IPA, 2) testing the validation of sound wave physics module based on REACT for class XI IPA, 3) testing the effectiveness of sound wave physics module based on REACT for class XI IPA. This study uses research and development procedures according to Nieven (2006) which includes 3 stages, namely: (1) Preliminary reseach (2) Prototyping stage, and (3) Assessment stage. The instruments used in this study were validation sheets and formative tests in the form of a description of the pre-test and post-test questions. Based on the results of the expert validation analysis, the category of very valid validity with reliability coefficient of 95.71% and the results of the user validation analysis obtained the category of validity is very valid with reliability coefficient of 92.86%. The results of the field test analysis obtained an average N-Gain score of 0.71 so that the module was declared effective to be used in learning on sound wave material for class XI IPA. Keywords : REACT, Validation, Effectiveness